APPLICATION OF SWAT MODEL IN HYDROLOGICAL SIMULATION OF A CATCHMENT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This survey explores the application of the Soil and Water Assessment Tool (SWAT) model in hydrological simulation within a catchment. SWAT, a widely-used hydrological model, is employed to simulate water flow, sediment transport, and nutrient dynamics in complex watershed systems. The study reviews recent applications of SWAT in diverse geographical and climatic settings, assessing its effectiveness in capturing spatiotemporal variations in hydrological processes. By synthesizing findings from various studies, this survey provides insights into the model's versatility, strengths, and limitations. The analysis aims to enhance understanding of SWAT's performance across different catchments, contributing to improved water resource management and informed decision-making in the face of changing environmental conditions.